Usage of academic social networking sites by Karachi social science faculty: Implications for academic libraries. (March 2018) - Ali, Muhammad Yousuf; Richardson, Joanna
The last decade has seen the emergence of academic social networking sites as a vehicle for scholars to promote their research and communicate with other scholars in their field. Given the small number of studies on the use of such sites by Pakistani academics, the authors conducted an exploratory study of social science faculty members at five Karachi (Pakistan) public sector universities. Analysis of the 68 valid responses revealed that the primary reason for accessing an academic social networking site was to search for articles on the site. Results also showed that accruing citations was the main reason for which respondents uploaded their own publications. The findings validate a role for librarians to support academics in their creation of effective online academic profiles.